Fenomena Alih Fungsi Lahan : Apakah Tenaga Kerja dapat Berpindah dari Sektor Pertanian Ke Sektor Lain ? Studi Kasus Kabupaten Bekasi - Meidy Haviz; Restu Suryaman; Reggy Tri (Jurnal Riset Ilmu Ekonomi, 2021)
The movement of workers from the agricultural sector to the industrial sector can occur along with the occurrence of industrialization. The question is whether the same transfer can occur when agricultural land suddenly changes the function to industrial land as is the case in many developing countries. To test this hypothesis, a study was carried out in a rural area not far from Jakarta. The respondents of this study are families who have sold part of the agricultural land they owned. Questions were asked through a questionnaire containing family members who might switch professions from farmers to employees of industrial companies. The data collected is processed using the logit regression model by using the backward stepwise regression method. The results of the study stated that the probability of movement of types of work is affected by the area of ​​land sold, education level, and income after working in the nonfarm sector.